Fagonia stabilized gold nanoparticles as antimicrobial agents. (20th August 2021) - Mariam, Rukhsana; Naz, Gul; Ramzan, Muhammad; Anjum, Muhammad Naeem; Anjum, Shazia; Abdullah, Muhammad
Abstract: In this study, gold nanoparticles (GNPs) were synthesized using an aqueous extract of Fagonia, as a stabilizing and reducing agent, applying the green approach. The phytochemicals present in Fagonia extract are responsible for the creation of GNPs. The reaction kinetics of Fagonia stabilized GNPs (FGNPs) was observed through the optical absorption spectra and the absorption maxima occurred at 547 nm. The face-centered cubic (FCC) nature of the GNPs was analyzed by the XRD pattern and average crystallite size ( D ) was measured about 10 nm. TEM images showed roughly spherical shapes of FGNPs. Evidence of successful formation of FGNPs was revealed by FTIR spectra of pure Fagonia and FGNPs. Fluorescence spectroscopic analysis of FGNPs exhibited a sharp red emission at about 700 nm. TGA technique showed a weight loss of about 19.3% in FGNPs confirming the presence of ligand onto the surface of GNPs. As-synthesized GNPs were investigated for their biomedical application i.e. antimicrobial activities against E. coli and Cocci . The eco-friendly prepared GNPs could play an important role in antimicrobial applications and their visible emission property may suggest the use of such FGNPs as potential biomarkers.